2020
DOI: 10.21203/rs.3.rs-19562/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decreased swallowing function in the sarcopenic elderly, without clinical dysphagia: a case-control study

Abstract: Background Sarcopenia and dysphagia have both become pivotal issues due to the increased number of elderly people. However, it’s still in question that whether sarcopenia, defined by the reduced handgrip strength and/or reduced gait speed, would necessarily results in pathological effects on swallowing function. Studies that focus on the subclinical changes of swallowing function of the sarcopenic elderly are lacking. In this study, we aimed to evaluate the swallowing function of the sarcopenic elderly withou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is possible that the gradual sub mental relaxation (increased offslope) in older individuals observed in the current study is associated with slow hyolaryngeal descent as a preventive strategy against secondary aspiration associated with large solid bolus swallows (1 cookie). A recent exploration of swallow related performance in healthy aging population reported reduced hyo-laryngeal ascend velocity in older individuals compared to younger [44]. Though our research does not directly measure the hyo-laryngeal velocity, the statistically insigni cant difference in the onslope measure indicate the speed of hyolaryngeal ascent may not be very different across the two groups.…”
Section: Discussionmentioning
confidence: 71%
“…It is possible that the gradual sub mental relaxation (increased offslope) in older individuals observed in the current study is associated with slow hyolaryngeal descent as a preventive strategy against secondary aspiration associated with large solid bolus swallows (1 cookie). A recent exploration of swallow related performance in healthy aging population reported reduced hyo-laryngeal ascend velocity in older individuals compared to younger [44]. Though our research does not directly measure the hyo-laryngeal velocity, the statistically insigni cant difference in the onslope measure indicate the speed of hyolaryngeal ascent may not be very different across the two groups.…”
Section: Discussionmentioning
confidence: 71%
“…For example, the study by Metheny et al has indicated that the risk of Aspiration increases due to sarcopenia, which reduces tongue propulsion (12). Also, some studies have demonstrated that older people have a reduction in laryngeal elevation, rotation, and forward movements which can delay airway closure and poor cough in the elderly (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic techniques provided by speech therapists include the use of compensatory strategies (change of diet, change of position) and rehabilitative exercises (muscle strengthening exercises or swallowing maneuvers) (1). Because the muscles used for swallowing can become weaker with age, in recent years, some studies have surveyed the effects of muscle strengthening exercises as the most common rehabilitative exercises for dysphagia therapy in the elderly (15)(16)(17). Robbins et al studied the Effects of Lingual Exercise on swallowing in ten older adults, and the results indicated significantly increased isometric and swallowing pressures (18).…”
Section: Introductionmentioning
confidence: 99%